How accounting for investment subsidies influences financial performance: an empirical analysis of IAS 20 and Czech accounting legislation - Radek Zdeněk; Jana Lososová; Jaroslav Svoboda (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
Our paper focuses on investment subsidies and the impact of accounting methods on financial ratios. Accounting for investment subsidies in Czechia is subject to national legislation and international accounting standards, such as the IAS20. This standard offers two options for capturing subsidies on assets – as deferred income or by reducing the book value. Czech accounting legislation allows only the second method mentioned. The essence of our article is to evaluate to what extent the alternative accounting of investment subsidies using accruals would be reflected in the financial ratios. The dataset consists of 277 enterprises that received an investment subsidy. Enterprises are from the agricultural sector that is subsidised for many reasons. The analysis is focused on testing the differences in the financial ratios according to financial statements compiled according to Czech accounting legislation and based on accounting allowed by IAS 20. The results indicate a higher significance of the subsidy for smaller companies. The impact of the change in the accounting procedure on financial ratios was statistically significant; on average, their values decreased by 2.8%. For the smallest businesses, the transition to accounting for subsidies using deferred income would be the most significant, with an average reduction of 5.5%.